Genotypic and phenotypic heterogeneity of Mycobacterium tuberculosis recovered from patients with pulmonary disease involving drug-resistant tuberculosis - Axcell, Amanda (My University, 2012)
Genetic heterogeneity of Mycobacterium tuberculosis demonstrating mixed infections or affecting single strains has been previously described. A single sputum culture from five patients with drug-resistant tuberculosis treated at Sizwe Hospital was analysed in-depth for genotypic and phenotypic heterogeneity. IS6110-based restriction fragment length polymorphism (RFLP) was performed on 20 colonies from each sputum for detection of mixed infections and clonal heterogeneity. No mixed infections were found, but IS6110-RFLP-linked clonal heterogeneity was observed in one patient. Drug susceptibility testing (DST) and sequencing of nine drug-resistance-associated genes performed on a total of 99 colonies from the five patients failed to show genotypic hetero-resistance. On DST, however, discordant rifampicin resistance findings were encountered in one patient. Minimal inhibitory concentrations performed on these colonies were close to the rifampicin critical concentration used for resistance determination, suggesting failure of the BACTEC MGIT 960 assay to reliably determine rifampicin susceptibility in strains with borderline resistance.
Degree of Master of Science in Medicine by Research Only Dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Medicine by Research. Johannesburg, 2012
Keywords: Mycobacterium Tuberculosis; Drug Resistance